Characteristics of Gracilaria sp. residue of seaweed sap extraction with extraction time treatment. (January 2020) - Nurhayati,; Basmal, J; Kusumawati, R; Melanie, S
Abstract: Seaweed sap has now been widely used as an organic fertilizer manufacturing material. The simple extraction process of seaweed sap allows the reuse of seaweed residue. This study was aimed to evaluate the effect of extraction time of Gracilaria sp. sap extraction to the characteristics of the residue. The extraction process was done with a variation in the extraction time of 0 (5 minutes), 2, 4, and 6 hours. Then, seaweed residue was obtained after the extraction seaweed sap was dried. The observed parameters were the yield, moisture, ash, and fat content of the seaweed residue. The results of the analysis were compared to dried Gracilaria sp. without seaweed sap extraction. The results show that the dried seaweed residue of all treatment had different moisture, ash, and fat content with the seaweed control. The highest yield of seaweed residue was obtained from the treatment 0 (5 minutes) hour of extraction (52.16%) with a moisture content of 10.41%, ash content of 12.39%, and fat content of 0.30%. These seaweed residues could potentially be used as biocomposite materials.